Blue rubber bleb naevus syndrome: A rare cause of gastrointestinal bleeding in an African child - Walter C; Mbebe T; Caragounis E; Thirsk I (African Journal of Paediatric Surgery, 2010)
Blue rubber bleb naevus syndrome (BRBNS) is characterised by vascular malformations of the skin and gastrointestinal tract. We present the rare case of BRBNS in an African child. She presented with large-volume gastrointestinal bleeding and was managed by on-table colonoscopic identification and surgical excision, of all her enteric, vascular malformations.